Control in robotics and automation sensor-based integration - Ghosh, B. K. 1936-; Xi, Ning; Tarn, Tzyh-Jong 1937- (Academic Press, 1999)
Microcomputer technology and micromechanical design have contributed to recent rapid advances in Robotics. Particular advances have been made in sensor technology that allow robotic systems to gather data and react "intelligently" in flexible manufacturing systems. The analysis and recording of the data are vital to controlling the robot. In order to solve problems in control and planning for a Robotic system it is necessary to meet the growing need for the integration of sensors in to the system. Control in Robotics and Automation addresses this need. This book covers integration planning and control based on prior knowledge and real-time sensory information. A new task-oriented approach to sensing, planning and control introduces an event-based method for system design together with task planning and three dimensional modeling in the execution of remote operations. Typical remote systems are teleoperated and provide work efficiencies that are on the order of ten times slower than what is directly achievable by humans. Consequently, the effective integration of automation into teleoperated remote systems offers potential to improve remote system work efficiency. The authors introduce visually guided control systems and study the role of computer vision in autonomously guiding a robot system. * Sensor-Based Planning and Control in an Event-Based Approach * Visually Guided Sensing and Control * Multiple Sensor Fuson in Planning and Control * System Integration and Implementation * Practical Applications
Includes bibliographical references and index. - Print version record
Keywords: Robots -- Control systems; Automatic control; Robots; Systèmes de commande; Commande automatique; TECHNOLOGY & ENGINEERING; Robotics; Robots; Control systems